Preliminary Study On Lightweight Interlocking Block Design - Cheong, Leonard Qi Lin (2020)
The interlocking block has been brought into the market as building units due to the setbacks of the conventional building units for construction. On account of the disadvantages confronted with conventional building units, for example, slow construction, dependence on skilled labourers and high logistics expenses. Also, conventional building units such as clay bricks have created a huge environmental problem during the manufacturing processes. Countries such as Bangladesh have been suffering a negative impact on food security as clay brick required and used up a huge amount of the topsoil. After all, the need for alternative units and sustainable materials is needed to be investigated. This study presented an overview of the development of the lightweight interlocking block in terms of the design, material and installation methods. The study aims to design and identify a sustainable material that is suitable to be incorporated for the proposed designed interlocking blocks. Meanwhile, all the interlocking blocks design is modelled utilised Autodesk Fusion 360 software. Besides, the consideration aspects for the interlocking block design included the constructability and elimination of the required trimming processes as compared to conventional building units. Besides, the reliability of the proposed material was conducted using SWOT analysis in this study. 4 types of interlocking blocks are designed, which is the full, half, full coping and half coping interlocking block. The sustainable material proposed to be used for the designed interlocking block is palm kernel shell concrete (PKSC), which is known as lightweight aggregate concrete. The data collection and analysis showed that the mix ratio of 1:1:3 and 1:1:2 comprising cement: sand: PKS is suitable to be adopted for the non-load-bearing and load-bearing wall respectively. Lastly, the installation method for the designed interlocking block comprised a total of 5 stages. Specifically, started with the base preparation, laying the first course, laying consequences courses, laying the final course and plaster or skim coat.